2020
DOI: 10.1101/2020.07.31.20166157
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

High prevalence of food insecurity, the adverse impact of COVID-19 in Brazilian favela

Abstract: Objective: To investigate food insecurity prevalence in two favelas in Brazil in the early weeks from physical distancing policy, between March 27, 2020 to June 1, 2020. Design: A cross-sectional study using online questionnaire to elicit information on socioeconomic and demographic characteristics, the types of stores visited to buy food and food insecurity screening. Experience of food insecurity was collected according to the Brazilian Food Insecurity Scale. Factors associated with moderate or severe food i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 16 publications
2
10
0
Order By: Relevance
“…Our findings strongly suggest that the COVID-19 pandemic is increasing food insecurity in Mexico on a monthly basis during the mandated lockdown. These results are consistent with previous studies that demonstrate how in vulnerable households food security declines during socio-economic shocks (4,5) and that as the pandemic advances food security can worsen even further (7,8) . Moreover, lockdowns associated with the pandemic might keep disrupting the food supply chain and food consumption patterns.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings strongly suggest that the COVID-19 pandemic is increasing food insecurity in Mexico on a monthly basis during the mandated lockdown. These results are consistent with previous studies that demonstrate how in vulnerable households food security declines during socio-economic shocks (4,5) and that as the pandemic advances food security can worsen even further (7,8) . Moreover, lockdowns associated with the pandemic might keep disrupting the food supply chain and food consumption patterns.…”
Section: Discussionsupporting
confidence: 93%
“…Yes/No). After computing the total summative score for the eight items, food (in)security was categorised into four levels: food security (total score = 0), mild food insecurity (1-3), moderate food insecurity (4-6) and severe food insecurity (7)(8). This method of estimation was followed in the current analysis; missing values for the food insecurity questions were minimal, with a maximum of 1•7 % in April.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These findings are consistent with other studies, for example, in Jordan (36) it was reported that people who had a monthly income per capita below the poverty line were more likely to have moderate food insecurity (OR: 5·33; 95% CI: 4·44–6·40) and severe food insecurity (OR: 6·87; 95% CI: 5·542–8·512). In the same way, other studies that explored the determinants of food insecurity in the pandemic contexts reported a higher risk to have MSFI in low-income people (37) , people who lost their job (14, 38) or people substantially lost their income (39) .…”
Section: Discussionmentioning
confidence: 72%